SIKAP MEMBERI PERSEMBAHAN MENURUT INJIL MARKUS 12:41-44 - David Susilo Pranoto (Manna Rafflesia, 2014)
This paper is titled" Attitude to Give Offerings According to the Gospel of Mark 12: 41-44 ". Mark's Gospel was written by Mark himself and this Gospel of Mark is the earliest Gospel written, which is between 65 and 70 AD before the Temple in Jerusalem was destroyed and Mark's Gospel is also the shortest of the four Gospels. This book was shown to the Jews to introduce Christ as a servant. Specifically the Gospel of Mark 12: 41-44 tells how Jesus showed His disciples the attitude of the rich and the widows of the poor in giving offerings. This shows that Jesus wanted to tell everyone and specifically to the students how the right attitude in giving offerings. The text Jesus shows about the attitude of the rich and poor widows in making offerings in the Temple. In addition, in the context of the Gospel of Mark 12: 41-44, Jesus showed His disciples the right attitude in offering. Jesus' purpose here is to direct the attention of His disciples to the poor widow. The poor widow gives more offerings than the offerings of rich people, because she gives from her shortcomings while rich people give from abundance. So through this article we can open the understanding of believers to have the right attitude to offer.